A life cycle analysis of novel lightweight composite processes: Reducing the environmental footprint of automotive structures. (1st January 2022) - Wegmann, Stephanie; Rytka, Christian; Diaz-Rodenas, Mariona; Werlen, Vincent; Schneeberger, Christoph; Ermanni, Paolo; Caglar, Baris; Gomez, Colin; Michaud, Véronique
Abstract: In this study, three novel thermoplastic impregnation processes were analyzed towards automotive applications. The first process is thermoplastic compression resin transfer molding in which a glass fiber mat is impregnated in through thickness by a thermoplastic polymer. The second process is a melt-thermoplastic Resin Transfer Molding (RTM) process in which the glass fibers are impregnated in plane with the help of a spacer. The third process, stamp forming of hybrid bicomponent fibers, coats the fibers individually during the glass fiber production. The coated fibers are used to produce a fabric, which is then further processed by stamp forming. These three processes were compared in a life cycle analysis (LCA) against conventional resin compression resin transfer molding with either glass or carbon fibers and metal processes with either steel or aluminum that can be new, partly or fully recycled using the case study of the production, life and disposal of a car bonnet. The presented LCA includes the main phases of the process: extraction and preparation of the raw materials, production and preparation of the mold, process, and energy losses. To include the life of the analyzed bonnet, the amount of diesel that is used to drive the weight of the bonnet for 300′000 km is calculated. In this LCA, the disposal of the bonnet is integrated by analyzing the used energy for the recycling and the incineration. The results show the potential of the developed thermoplastic impregnation processes producing automobile parts, as the used energy producing a thermoplastic bonnet is in the same range as the steel production. Highlights: Comparison of the energy demand of three new thermoplastic impregnation processes. High environmental potential of thermoplastic composites compared to metal parts. Comparison of the environmental impact of virgin, partly and fully recycled metals. Novel thermoplastic impregnation processes are relevant for the automotive sector.